Enhancing work-life balance: a comparison of generational expectations and organizational practices - Aslam, Abu Bakar Sidiq (2025)
This study investigates generational differences in work-life balance expectations and organizational practices in Singapore's unique multicultural business environment. Through semi-structured interviews with 12 professionals across Generation X, Millennials, and Generation Z, alongside policy makers, the research reveals distinct generational approaches to work-life integration. Generation X participants emphasize family provider roles with evolving spiritual dimensions, Millennials focus on efficiency and clear boundaries, while Generation Z demonstrates the strongest preference for complete work-life separation and digital boundary management. The findings highlight how these differences intersect with Singapore's cultural context, where traditional Asian values of filial piety and collective responsibility create additional dimensions to work-life balance expectations.